Inauguration of memory: a place to be born - Elizaberta López Pérez (Arteterapia)
There are described some experiences developed in different meetings in two workshops of art therapy: the Workshop of Art and Painting, an optional subject of the fi rst cycle of the program that the Permanent Classroom of Permanent Training, in Granada University, dedicates to persons 50 years old; and the workshop of the Therapeutic Community of North Area of Hospital Virgen del las Nieves, Granada, which users, patients of chronic character, are frequently schizophrenics.